Power and Epistemology: How the Western Idea of “Nation” Triumphed Over Its Indigenous Counterparts - Uddin, Mohammad Moin (Kathmandu School of Law Review, 2024)
The Peace of Westphalia and the French Revolution are two constitutive moments of the modern idea of “nation”. The modern idea of "nation" is linked with the idea of statehood. This idea spread throughout Europe and became dominant worldwide during the heydays of European colonialism. International law, shaped by Western powers, endorsed the idea, and imposed it upon the rest of the world. Nations not claiming statehood existed before the European age of nationalism, while thousands of them still exist today in the form of “nations-within,” but most independent states do not recognize such nations. Independent states call these nations ‘communities,’ ‘societies,’ ‘ethnic groups,’ ‘gens,’ ‘tribes,’ or even ‘confederacies’—anything but nation. This paper argues that the dominance of the western idea of nation happened for two reasons: first, the triumph of European powers who believed in the superiority of western ideas, and second, the resilience and sustainability of European epistemology even after the decolonization. However, it remains a reality that non-state nations demonstrated extraordinary resilience too, surviving perennial threats and assaults from state power. Indigenous nations are prime examples of such resilience. Indigenous peoples of North America are legally recognized as nations, though indigenous peoples of Asia and Africa are denied such recognition. In this article, the author explores different trajectories of indigenous people who encounter with colonizers in settler states and in the Third World and concludes that ‘nations-within’ should be recognized with respect.